Control de las principales Moscas de la Fruta en el Cultivo de Naranja (Citrus sinensis) - Guanoluisa Caicedo, María Fernanda (2020)
This research is based on collecting information on the main fruit flies that affect the cultivation of orange, different sources of information compile that this crop is of economic importance, since they contribute to the food of the world and national population. Ecuador has the potential to produce citrus fruits, mainly in the coastal region, growing 10,219 ha in monocultures (orange, lemon, tangerine) and 58,119 ha in association. The most producing provinces are Manabí, Los Ríos, Bolívar, Guayas, Pichincha and Tungurahua. Its performance is permanently threatened by phytosanitary problems, including arthropod-plague. According to the sources consulted, they report that the main flies that affect the cultivation of orange are (Ceratitis capitata) and (Anastrepha fraterculus) these incest’s develop rapidly and their highest incidence is in their larval state causing losses for farmers. There are different controls that can be of great help to obtain a free or controlled crop of fruit flies. In this research we talk about the different types of controls which will be mentioned, Natural control, Biological control, Cultural control, Chemical control, Physical control, Sterile Insect Technique (TIE), Self-control, Integrated control, managed agricultural systems and Legal Control Another important fact is that different types of tricks can also be used to control fruit flies.